A survey on vocabulary learning strategies employed by ESL learners - Esa, Zaleha; Zakaria, Zarina Ashikin (2014)
Vocabulary is an important component of language proficiency that provides the root for the ability of the learners is speaking, listening, reading and writing. the importance of vocabulary is esential for language learners. however, the teaching of vocubalury is often neglected in the teaching and learning of English language and it was often given little priority in language programmes and received only incidental attention in textbook and language programmes (Hedge, 2008). Many languages teachersthink that vocabulary cab be left on its own and does not need to be taught perhaps due to several reasons such as grammar should be emphasized more than vocabulary students would make mistakes in sentence construction if too many words were learned before basic grammar has been mastered, and word meanings can be learned through experience and cannot be taught in the class room. Having the limited vocabulary and strategis often impede learners in displaying their abilities and discourage them making use of language learning opportunities around then such as watching television, listening to the radio, reading or using the language in different contexts. Due lack of vocabulary, learners cannot perform in spoken and written in which they are less confident to speak and write in the target language. This study surveys the vocabulary learning strategies employed by a group of ESL learners of a higher institution in Malaysia. Suggestion on the pedagogical implication are provided to supplement the ESL educators in dealing with various vocabulary learning strategies employed by the learners.